A view of the Lower to Middle Paleolithic boundary from Northern France, far from the Near East?. Issue 145 (August 2020) - Hérisson, David; Soriano, Sylvain
Abstract: Northern France and the Near East play and have played a central role in the debate around the Lower Paleolithic (LP) to Middle Paleolithic (MP) boundary. In the early 1990s, the renewed Saalian record for Northern France began to outline a mosaic model of the LP-to-MP transition—mainly based on Tuffreau's works. It implied the coexistence of Upper Acheulean assemblages (numerous bifaces with few standardized retouched flakes), 'Epi-Acheulean' assemblages (rare bifaces and diversified retouched flakes), and Mousterian assemblages (Levalloisian industries) during the Marine Isotope Stage (MIS) 8–6 period. Since the 2000s, the discovery of new key sites and enhanced field and laboratory methods are challenging this model. We present first a brief historical summary of previous approaches to the LP to MP boundary in Northern France. A large data set of Saalian archaeological units available from previous works has been updated and expanded to include additional sites. This allows us to demonstrate that the current Saalian record from Northern France is both rich and sparse as it is heterogeneously biased through time and space and that these biases limit the accuracy of any attempt to model the LP-to-MP transition. Nevertheless, we describe the differences between pre-MIS 9 and MIS 9 and MIS 8–6 records for lithic industries and discuss whether the current periodization is still relevant considering new data on technological, behavioral, and cultural changes. The comparison between Northern France and Near Eastern records allows regional cultural patterns to be distinguished from global trends in lithic trajectories of change and determination of how they slotted together. Our review of the available data from these two distant regions confirms that the LP-to-MP transition is probably one of the major cultural shifts in human evolution.